Existing barriers of using of active degassing systems for municipal solid waste disposal sites to solve environmental and climatic problems in the Republic of Belarus - Bertosh, Evgenia; Gonchar, Kristina; Melekh, Dmitry; Narkevich, Ivan; Fursa, Yulia (Journal of the Belarusian State University. Ecology, 2024)
Modern cities are a major source of solid municipal waste (MSW) generation, the volume of which is increasing from year to year due to growing economic development and urbanization. The most common method of solid waste disposal worldwide, including in the Republic of Belarus, is it’s landfilling. Currently, there are 151 landfills in Belarus for the placement of MSW, where about 65 % of the generated MSW in the country is buried [1], which has a negative impact on the environment and climate change. As a part of the implementation of international obligations to implement the provisions of the Paris Agreement to the UN Framework Convention on Climate Change, the Council of Ministers of the Republic of Belarus adopted a resolution dated September 29, 2021. No. 553 «On establishing a nationally determined contribution of the Republic of Belarus to reduce greenhouse gas emissions by 2030», according to which the country undertakes to reduce greenhouse gas (GHG) emissions by 2030 by 35 percent to the level of 1990, taking into account the absorption in the sector «Agriculture, Forestry and Other Land Use». The Republic of Belarus fulfills its obligations under the Paris Agreement and takes measures to reduce anthropogenic GHG emissions. Greenhouse gas emissions in the Waste sector amounted to 6.5 % of total emissions in 2021 and increased by 32 % over the period 1990–2021 (from 4513.5 Gg in CO2 equivalent to 5975.9 Gg) due to growth of methane emissions from landfills of municipal solid waste. The article considers a number of environmental and socio-economic advantages of using active degassing systems for solid waste disposal sites and the use of landfill gas for the production of electric energy. The most dangerous effects on various components of the natural environment, including groundwater and surface waters, soils, and atmospheric air, which have toxic substances contained in the filtrate of solid waste disposal sites and included in the landfill gas released as a result of anaerobic decomposition of waste, are described. The amount of prevented emissions of pollutants due to their capture by active degassing systems at one of the facilities of the Republic of Belarus have been calculated. The normative legal acts supporting the development of technologies for the production and utilization of biogas in the Republic of Belarus and international documents implemented by the country within the framework of the global climate agenda, including the United Nations Framework Convention on Climate Change and the Paris Agreement, are considered.